Generating Rational Loop Groups with Noncompact Reality Conditions - Goertsches, Oliver (MATHEMATICA SCANDINAVICA, 2013)
We find generators for the full rational loop group of GL(n,C) as well as for the subgroup consisting of loops that satisfy the reality condition with respect to the noncompact real form GL(n,R). We calculate the dressing action of some of those generators on the positive loop group, and apply this to the ZS-AKNS flows and the n-dimensional system associated to GL(n,R)/O(n).